2003
DOI: 10.1136/adc.88.11.1009
|View full text |Cite
|
Sign up to set email alerts
|

Empyema thoracis: a 10-year comparative review of hospitalised children from south Asia

Abstract: Aims: To study the clinical and microbial profile of childhood empyema in South Asia and to identify the changes over the past three decades. Methods: A total of 265 children (aged 1 month to 12 years) with empyema admitted to the Advanced Pediatric Center, PGIMER, Chandigarh, India in 1989-98, were reviewed retrospectively. Results and Conclusions: One third of children were under 5. Culture positivity had decreased significantly (48% v 75%) over the years. Staphylococcus aureus continues to be the commonest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
58
10
6

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(91 citation statements)
references
References 25 publications
17
58
10
6
Order By: Relevance
“…The present analysis shows that most cases were in children below 5 years, thus confirming that empyema may be more likely to occur in young children. Previous studies from India also show similar results [10]. The average age of presentation in the present study was similar to previous studies [11][12][13].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The present analysis shows that most cases were in children below 5 years, thus confirming that empyema may be more likely to occur in young children. Previous studies from India also show similar results [10]. The average age of presentation in the present study was similar to previous studies [11][12][13].…”
Section: Discussionsupporting
confidence: 93%
“…Yield of culture was significantly lower (32%) compared to reports from other developing countries (48-82%) [10,[14][15][16][17][18]. It could be due to prior use of antibiotics and late referral.…”
Section: Discussioncontrasting
confidence: 59%
“…Previous studies suggest a success rate of 61-100% with chest tube drainage and antibiotics. (39,40) These treatment outcome were similar to other studies. (21,29) A meta-analysis comparing operative and non-operative procedures has also concluded that conservative management leads to recovery in more than 76% of the patients.…”
Section: Discussionsupporting
confidence: 79%
“…In a recent study from India it was shown that of the 250 pyoderma cases from the community 80.8% was due to S. aureus, of which 10.9% was MRSA; 54.4% of the patients carried S. aureus in their nares, 11.8% being resistant to methicillin [131]. Among agents of community acquired thoracic empyema of children in an Indian study S. aureus was the most frequently identified pathogen and from 3 children MRSA was isolated [132]. Unfortunately, none of these studies has been complemented with molecular typing data to confirm typical CA-MRSA genotypes and some use only phenotypic surrogate markers, as clindamycin susceptibility, to define "community-acquired-like" isolates [133].…”
Section: Staphylococcus Aureusmentioning
confidence: 99%